AKUNTABILITAS PENGELOLAAN WAKAF PADA BAITUL MAAL HIDAYATULLAH PROVINSI BENGKULU - Henawati; Fadli (JURNAL FAIRNESS, 2021)
Accountability is important for a waqf management institution. There arevarious ways an institution can demonstrate accountability. This study aims to describethe practice of the accountability of waqf management at Baitul Maal HidayatullahBengkulu. This type of research is a qualitative research with descriptive qualitativeresearch type. This study focuses on 5 accountability mechanisms, namely reportingand disclosure, performance appraisal and evaluation, participation, self-regulation andsocial auditing.The results show that in reporting and disclosure, the financial statements ofwaqf use PSAK 109 and are consolidated with the central Baitul Maal Hidayatullah,data recording of waqf assets in the form of immovable assets is submitted to thedepartment of waqf assets and reports are submitted through various media. In theperformance appraisal and evaluation accountability mechanism, Baitul MaalHidayatullah carries out an evaluation once a month and uses Key PerformanceIndicators as performance appraisal indicators. In the participatory accountabilitymechanism, Baitul Maal Hidayatullah management publishes program plans throughvarious media, involves observers in the implementation of the waqf program, involvesall administrators in institutional decision making. In the self-regulation accountabilitymechanism, the Baitul Maal Hidayatullah administrators provide rewards andpunishments to improve the performance of the management and consult with theRegional Leadership Council and the central Baitul Maal Hidayatullah in resolving waqfproblems. In the social audit accountability mechanism, the management of Baitul MaalHidayatullah provides special media for community aspirations, plays a role in helpingsocial problems and is already responsible for the waqf mandated by the supervisor.